Modification of superoxide dismutase 1 (SOD1) properties by a GFP tag--implications for research into amyotrophic lateral sclerosis (ALS). - James C Stevens; Ruth Chia; William T Hendriks; Virginie Bros-Facer; Jan van Minnen; Joanne E Martin; Graham S Jackson; Linda Greensmith; Giampietro Schiavo; Elizabeth M C Fisher (PLoS ONE)
Background Since the discovery that mutations in the enzyme SOD1 are causative in human amyotrophic lateral sclerosis (ALS), many strategies have been employed to elucidate the toxic properties of this ubiquitously expressed mutant protein, including the generation of GFP-SOD1 chimaeric proteins for studies in protein localization by direct visualization using fluorescence microscopy. However, little is known about the biochemical and physical properties of these chimaeric proteins, and whether they behave similarly to their untagged SOD1 counterparts. Methodology/principal findings Here we compare the physicochemical properties of SOD1 and the effects of GFP-tagging on its intracellular behaviour. Immunostaining demonstrated that SOD1 alone and GFP-SOD1 have an indistinguishable intracellular distribution in PC12 cells. Cultured primary motor neurons expressing GFP or GFP-SOD1 showed identical patterns of cytoplasmic expression and of movement within the axon. However, GFP tagging of SOD1 was found to alter some of the intrinsic properties of SOD1, including stability and specific activity. Evaluation of wildtype and mutant SOD1, tagged at either the N- or C-terminus with GFP, in PC12 cells demonstrated that some chimaeric proteins were degraded to the individual proteins, SOD1 and GFP. Conclusions/significance Our findings indicate that most, but not all, properties of SOD1 remain the same with a GFP tag.